New graduate nurses' understanding and attitudes about patient safety upon transition to practice. Issue 13 (20th March 2019) - Murray, Melanie; Sundin, Deborah; Cope, Vicki
Abstract: Aims: To explore the transition experiences of newly graduated registered nurses with particular attention to patient safety. Background: New graduate registered nurses' transition is accompanied by a degree of shock which may be in tune with the described theory–practice gap. The limited exposure to clinical settings and experiences leaves these nurses at risk of making errors and not recognising deterioration, prioritising time management and task completion over patient safety and care. Design: Qualitative descriptive approach using semi‐structured interviews. Methods: Data were collected during 2017–18 from 11 participants consenting to face‐to‐face or telephone semi‐structured interviews. Interviews were transcribed verbatim, and data were analysed using thematic analysis techniques assisted by Nvivo coding software. The study follows the COREQ guidelines for qualitative studies (see Supplementary File1 ). Results: Key themes isolated from the interview transcripts were as follows: patient safety and insights; time management; making a mistake; experiential learning; and transition. Medication administration was a significant cause of stress that adds to time management anguish. Although the new graduate registered nurses' clinical acumen was improving, they still felt they were moving two steps forward, one step back with regards to their understanding of patient care and safety. Conclusion: Transition shock leaves new graduate registered nurses' focused on time management and task completion over patient safety and holistic care. Encouragement and support needed to foster a safety culture that foster safe practices in our new nurses. Relevance to practice: Having an understanding of the new graduate registered nurses' experiences and understanding of practice will assist Graduate Nurse Program coordinators, and senior nurses, to plan and provide the relevant information and education during these initial months of transition to help mitigate the risk of errors occurring during this time.